Evaluation of the Suitability of the Euphrates River water for Drinking and Irrigation purposes in Haditha City, Western Iraq - Mahmood H. D. Al-Kubaisi; Sufyan K. Al-Sumaidai (Tikrit Journal of Pure Science, 2023)
The supply of freshwater is essential to life, socio-economic development, and political stability in the Middle East. Recently, Iraq's rivers have experienced extreme shortage water scarcity as a result of climate change, as evidenced by the rarity of rainfall and high temperatures. To assess the Euphrates river water for drinking and irrigation uses in Haditha city, Ten water samples were collected in the study region and analyzed for major ions. It was established that water samples in the study region are considered freshwater, low enrichment of salts, and slightly alkaline water. Piper diagram indicates the overall samples belong to class1 (Mg 2+, Ca 2+, SO4 2-, Cl -) and category I (Ca 2+ - Mg 2+ and SO4 2- - Cl -), calcium chloride type (permanent hardness). The Water Quality Index shows that water samples are suitable for drinking purposes. All water sample is suitable for irrigation in the study region.